Preparation and characterization of solidified oleanolic acid-phospholipid complex aiming to improve the dissolution of oleanolic acid - Xiaoxu Yang; Qikun Jiang; Ping Du; Juanhang Zhao; Tianhong Zhang (Elsevier, 2016)
The purpose of this study was to prepare the oleanolic acid-phospholipid complex (OA-PC) and then solidify it employing fumed silica by simple solvent evaporation technique to improve dissolution rate of oleanolic acid and oleanolic acid-phospholipid complex. The process of OA-PC was optimized and the type and proportion of fumed silica were studied by dissolution text. The structures of the phospholipid complex and solidified powder were also characterized by differential scanning calorimetry, X-ray diffraction, and scanning electron microscope. In the dissolution tests, OA from solidified powder was further released compared with that from pure OA and OA-PC in different kinds of dissolution media. These results suggest that the method of preparing solidified powder of oleanolic acid-phospholipid complex is suitable for enhancing the dissolution rate of OA and OA-PC.